Potential For Solar Energy Utilization On The Rooftop Of The Amamapare Polytechnic Campus Building In Timika - Raya Pasangkunan; Nursahar Buang; Aryani Rombekila; Monika Seruni; Sukmawati Yusuf (MULTITEK INDONESIA, 2025)
This study analyzes the potential for solar energy utilization through a rooftop solar power system at the Amamapare Polytechnic campus in Timika, Central Papua, using PVsyst-based simulations. The designed system consists of 77 solar panels, 28 batteries, and 5 inverters, and is capable of producing 11,103 kWh/year, which only meets 19-20% of the total load, so that some of the energy still depends on PLN. The initial investment cost of the system is estimated at IDR 490,733,150, while the total life cycle carbon emissions are recorded at 20,702 kgCO2, reflecting the initial carbon footprint from production and installation. The results of the study show that rooftop solar power plants can significantly reduce dependence on fossil fuels and lower carbon emissions, while providing practical guidance for educational institutions in Papua to design sustainable independent energy systems. Keywords: Rooftop Solar Power Plant, Solar Energy, PVsyst, Independent Energy, Campus Building